Ironing Out the Conflicts: Iron Supplementation Reduces Negatives Bacterial Interactions in the Rhizosphere of an Atacama-Endemic Perennial Grass - Maldonado-Soto, J (BioMed Central Ltd, 2025)
Background: In plants, root exudates selectively influence the growth of bacteria that colonize the rhizosphere. Bacterial communities associated with root systems are involved in macro and micronutrients cycling and organic matter transformation. In particular, iron is an essential micronutrient required for the proper functioning of iron-containing enzymes in processes such as photosynthesis, respiration, biomolecule synthesis, redox homeostasis, and cell growth in plants. However, the impact of changes of iron availability on the structure and set of ecological interactions taking place in the rhizosphere remains poorly understood. In this study, field experiments were conducted to compare the effects of iron supplementation (0.1 and 0.5 mM of FeSO4) on the assembly of the bacterial community of rhizosphere soil and bulk soil in a perennial grass present in the Andes steppe of Atacama Desert. Results: The results indicated that the difference in beta diversity between bulk soil and rhizosphere soil detected before supplementation did not persist after iron supplementation, in addition, co-occurrence networks showed a significant reduction in negative interactions among soil bacteria, mainly in rare taxa (< 0.1% relative abundance). Conclusions: These observations suggest that iron availability contributes to the differentiation between bulk soil and rhizosphere bacterial communities, a process that is linked to significant changes in the relative abundance of more abundant species (> 0.1% relative abundance) and with a decrease in the negative interactions in both compartments after metal exposure. The differential effect of iron on the competition/cooperation ratio between bulk soils and the rhizosphere microbiome supports the hypothesis that the host limits the degree of cooperation that can be achieved by the bacterial community associated with an organ dedicated to nutrient absorption. © The Author(s) 2024.